2017
DOI: 10.1016/j.neuroimage.2017.05.062
|View full text |Cite
|
Sign up to set email alerts
|

Linking dopaminergic reward signals to the development of attentional bias: A positron emission tomographic study

Abstract: The attention system is shaped by reward history, such that learned reward cues involuntarily draw attention. Recent research has begun to uncover the neural mechanisms by which learned reward cues compete for attention, implicating dopamine (DA) signaling within the dorsal striatum. How these elevated priority signals develop in the brain during the course of learning is less well understood, as is the relationship between value-based attention and the experience of reward during learning. We hypothesized tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

12
38
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 56 publications
(50 citation statements)
references
References 55 publications
12
38
0
Order By: Relevance
“…Two recent PET studies, where dopamine release was measured while participants performed visual search tasks, suggest a relationship between dopamine signaling within the striatum and the control of visual attention (B. A. Anderson et al, 2016(B. A. Anderson et al, , 2017.…”
Section: Discussionmentioning
confidence: 99%
“…Two recent PET studies, where dopamine release was measured while participants performed visual search tasks, suggest a relationship between dopamine signaling within the striatum and the control of visual attention (B. A. Anderson et al, 2016(B. A. Anderson et al, , 2017.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, the behavioral impact of intertrial reward priming has been shown to positively correlate with a midline anterior ERP component, called medial frontal negativity, which has been suggested to reflect the assessment of motivational impact (Gehring & Willoughby, 2002 ; Hickey et al, 2010a ). The extent to which Anderson and colleagues (Anderson, Kuwabara, et al, 2017 ) observed VDAC during the test session was positively correlated with the dopamine release in the right anterior caudate during the training. In other words, more dopamine release throughout the training predicted more distraction during the test.…”
Section: Attention and Rewardmentioning
confidence: 93%
“…Associative reward learning can change the attentional priority of visual stimuli, such that learned predictors of reward acquire the ability to automatically capture attention. This phenomenon, referred to as value-driven attentional capture, is supported by covert attention measures (e.g., Anderson, Laurent, & Yantis, 2011a, 2011bFailing & Theeuwes, 2014), eyetracking (e.g., Anderson & Yantis, 2012;Le Pelley, Pearson, Griffiths, & Beesley, 2015;Theeuwes & Belopolsky, 2012), and stimulus-evoked brain activity using a variety of techniques, including functional magnetic resonance imaging (Anderson, 2017;Anderson, Laurent, & Yantis, 2014;Hickey & Peelen, 2015;Krebs, Boehler, Egner, & Woldorff, 2011), electroencephalography (MacLean & Giesbrecht, 2015;Qi, Zeng, Ding, & Li, 2013), positron emission tomography (Anderson, Kuwabara, et al, 2016;Anderson, Kuwabara, et al, 2017), and magnetoencephalography (Donohue et al, 2016;Hopf et al, 2015). Importantly, previously reward-associated cues have been shown to capture attention even when they are currently task-irrelevant and physically nonsalient, suggesting that reward history plays a direct role in the control of attention (see Anderson, 2013Anderson, , 2016a.…”
mentioning
confidence: 99%